Effect of isovalent substitution on structure of the two-slab BaNd2-xSmxIn2O7 indates - Titov, Y.A.; Belyavina, N.M.; Slobodyanik , M.S.; Nakonechna, O.I.; Strutynska , N.Yu.; Chumak , V.V. (Physics and Chemistry of Solid State, 2022)
The conditions of isovalent substitution of Nd atoms for Sm atoms in A-positions of the BaNd2In2O7 two-slab perovskite-like structure of the BaNd2-xSmxIn2O7 type (0 £ x £ 1.8) have determined by X-ray powder diffraction methods. Tetragonal crystal structure (space group P42/mnm) of the BaNd2-xSmxIn2O7 phases with substitution degree of Nd atoms equal to 0.5, 1.0, 1.5 and 1.8 was determined by the Rietveld method. Crystal structure of BaNd2-xSmxIn2O7 is based on the two-dimensional (infinite in the XY plane) perovskite-like blocks, consisting of two slabs of the deformed InO6 octahedra connected by vertices. Ba atoms are localized only at 4f position inside the perovskite block, while REE atoms are placed only at 8j position at the boundary of the perovskite block. The adjacent perovskite-like blocks are separated by a slab of LnO9 polyhedra and held together by - O - Ln - O - interblock bonds. It is established that the isovalent substitution of Nd atoms by smaller Sm atoms leads to a decrease in the length of the Ln - O2 distance (from 0.230(2) nm to 0.206(2) nm) and to an increase in the degree of deformation of the interblocks of LnO9 polyhedra, the inner block polyhedra BaO12, and the InO6 octahedra as well. Such structural changes destabilize the interblock "stitching" and are one of the main destruction factors of the slab perovskite-like structure of the BaNd2-xSmxIn2O7 phases at x > 1.8. Data obtained could be used for directed regulation of structure-sensitive properties of materials based on the BaNd2In2O7 indate.